ANALISIS PERBANDINGAN PELAFALAN PLOSIF b-p d-t dan g-k DALAM BAHASA MANDARIN DAN BAHASA INDONESIA - Sherlifia yarso; Lily Thamrin; Lusi Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractIn learning a language we need to understand many aspects of that language, especially mandarin which if the pronunciation is wrong will have different meanings. In madarin there are many different types of pronunciation. In Mandarin and Indonesian have the same consonants, but the pronunciation method is different. The result is that Indonesians against consonants in Indonesian b-p, d-t and g-k often don't fit the pronunciation because they are influenced by mother languange, for example: Indonesian students when they learn mandarin’s pronouncation like b-p, d-t and g-k in Indonesian, they will read it with Indonesian pronounce,even Mandarin’s pronouncation are different. Mandarin and Indonesian both have inhibitory consonants. In Mandarin there are aspirational and non-aspirational sounds, in Indonesian there are "voiced" and "voiceless". This includes differences in mandarin and Indonesian. The equivalent of Mandarin and Indonesian they use the alphabet to express a word. In mandarin are named Pinyin, the mandarin character named Hanzi. Keywords: b – p d – t       g – k    Consonant analysis     se yin